Politik Hukum Kelembagaan Pengelolaan Zakat Dalam UU No. 21 Tahun 2008 Dan UU No. 23 Tahun 2011 - Adiyes Putra; Nurnasrina (LPPM STAI Diniyah Pekanbaru, 2020)
The process of making the Draft Law on Islamic banking and the Draft Management Act on zakat becoming a law that is legal and legal goes through a long process. In the process, there was a tug of war between those who supported the formation of the law and those who disagreed with the issue of Islamic banking and the management of zakat formally regulated in the form of laws. It must be recognized that the formation of laws is influenced by the level of community development, the level of the economy, culture, science and technology, and religious beliefs in a society. Of the 10 factions in the legislature, 9 factions stated their approval of the Draft Law on Sharia banking and the Draft Management Act on zakat being ratified into law, and there was one faction that rejected it namely the F-PDS. Although there was a rejection from 1 faction, the legislative and the President finally passed the Sharia banking Act by enacting Law Number 21 the Year 2008 on Sharia Banking on June 17, 2008, and its promulgation by the President on July 16, 2008. Next, Islamic leaders and observers zakat urge the government to immediately amend Law No. 38 of 1999. At the insistence of that later and the legislature and the government ratified Law Number 23 of 2011 concerning Management of Zakat in place of Law Number 38 of 1999.